Politiche pubbliche di promozione della salute mentale tra condizioni locali e proposte delle agenzie internazionali: il caso di Medellín (2006)
ABSTRACT: The article presents a program aimed to foster mental health promotion in the Moravia district of Medellín city, characterized by major economic, environmental, housing, and psychosocial problems. The program is based on the concept and tools of human sustainable development, and on the empowerment of people and social actors, which are active parts in controlling health determinants. It is supported by the national government and is coherent with UN and WHO principles and recommendations for mental health programs.